2017
DOI: 10.3382/ps/pew489
|View full text |Cite
|
Sign up to set email alerts
|

In-ovo monochromatic green light photostimulation enhances embryonic somatotropic axis activity

Abstract: Previous studies demonstrated that in ovo photostimulation with monochromatic green light increases body weight and accelerates muscle development in broilers. The mechanism in which in ovo photostimulation accelerates growth and muscle development is not clearly understood. The objective of the current study was to define development of the somatotropic axis in the broiler embryo associated with in ovo green light photostimulation. Two-hundred-forty fertile broiler eggs were divided into 2 groups. The first g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Previous studies have demonstrated that the monochromatic green light promotes the pineal gland releasing MEL [27] and improving hepatic IGF-I synthesis and secretion, which finally accelerated the broiler growth rate [3,4,6,28]. The increased IGF-I promoted satellite-cell proliferation and differentiation [6,9], which was responsible for muscle growth [29]. In this study, GL elevated plasma MEL secretion, and this was also accompanied by increases of Mel1c and IGF-I mRNA levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the monochromatic green light promotes the pineal gland releasing MEL [27] and improving hepatic IGF-I synthesis and secretion, which finally accelerated the broiler growth rate [3,4,6,28]. The increased IGF-I promoted satellite-cell proliferation and differentiation [6,9], which was responsible for muscle growth [29]. In this study, GL elevated plasma MEL secretion, and this was also accompanied by increases of Mel1c and IGF-I mRNA levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the role of light spectra in chicken growth in recent years, finding that different wavelengths of light affected the growth of turkeys [1] and broilers [2,3]. Furthermore, green light (GL) stimulation has been shown to accelerate muscle growth in broilers [4], and enhance the secretion of insulin-like growth factor I (IGF-I) by chick embryo hepatocytes [5,6]. IGF-I has been shown to be a key regulator of muscle development and metabolism in birds and other vertebrate species [7,8], and promoted satellite cells proliferation through IGF-I signaling [9].…”
Section: Introductionmentioning
confidence: 99%
“…Liang [44] showed an increase in GHRH expression from 16 days of incubation until 1-day post-hatching. GL photostimulation from ED15 increased hypothalamic GHRH mRNA expression to that of the positive control [5,45]. Accordingly, this may explain the increase in brain weight, neurons, and BI observed in the groups exposed to light compared with the control group.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies demonstrated that exposing fertile eggs to light can increase the growth of the embryo and decrease the incubation period [2][3][4]. Post-hatch artificial lighting is an important management method for the growth and muscle development of meat-type birds [5]. Embryo exposure to light leads to changes in metabolic rate [6], such as an increase in embryo metabolic rate in the pigeon Columba livia in light compared with darkness [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in several studies, including our previous papers, that in ovo GL photostimulation elevate the expression and secretion of different components of the somatotropic axis ( Halevy et al., 1998 ; Zhang et al., 2014a , 2014b ; Dishon et al., 2017 ; Dishon et al., 2018 ). In our previous paper ( Dishon et al., 2021 ), we discovered that in ovo GL photostimulation of broiler embryos from embryonic day ( ED ) 18 until hatching (hatching period), showed similar elevation in somatotropic axis activity, manifested by increased plasma GH levels and hypothalamic GHRH and liver GHR and IGF-1 mRNA levels on the day of hatching.…”
Section: Introductionmentioning
confidence: 88%